2022
DOI: 10.3389/fpls.2022.916550
|View full text |Cite
|
Sign up to set email alerts
|

Pan-genome analysis of three main Chinese chestnut varieties

Abstract: Chinese chestnut (Castanea mollissima Blume) is one of the earliest domesticated plants of high nutritional and ecological value, yet mechanisms of C. mollissima underlying its growth and development are poorly understood. Although individual chestnut species differ greatly, the molecular basis of the formation of their characteristic traits remains unknown. Though the draft genomes of chestnut have been previously released, the pan-genome of different variety needs to be studied. We report the genome sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 104 publications
2
10
1
Order By: Relevance
“…A total of 421.37 Mb of the sequence was annotated as repetitive sequences in the genome assembly of cultivar 'Tsukuba', which was similar to the genome assembly of cultivar 'Ginyose' (Shirasawa et al, 2021). The two Japanese chestnut genome assemblies exhibit a repetitive rate similar to that of the genome assembly of Chinese chestnut (431.41 Mb,55.74%;437.75 Mb,64.38%;423.16 Mb,53.49%;442.76 Mb,64.43%) described by Sun et al (Sun et al, 2020) and Hu et al (Hu et al, 2022), but slightly different from that found in research by Wang et al (366.84 Mb,53.24%) (Wang et al, 2020b) and Xing et al (390 Mb,49.69%) (Xing et al, 2019). This difference might be caused by the exclusion of duplicated contigs in our research or the use of different annotation methods.…”
Section: Annotation and Evolutionary History Of The Japanese Chestnut...supporting
confidence: 74%
See 4 more Smart Citations
“…A total of 421.37 Mb of the sequence was annotated as repetitive sequences in the genome assembly of cultivar 'Tsukuba', which was similar to the genome assembly of cultivar 'Ginyose' (Shirasawa et al, 2021). The two Japanese chestnut genome assemblies exhibit a repetitive rate similar to that of the genome assembly of Chinese chestnut (431.41 Mb,55.74%;437.75 Mb,64.38%;423.16 Mb,53.49%;442.76 Mb,64.43%) described by Sun et al (Sun et al, 2020) and Hu et al (Hu et al, 2022), but slightly different from that found in research by Wang et al (366.84 Mb,53.24%) (Wang et al, 2020b) and Xing et al (390 Mb,49.69%) (Xing et al, 2019). This difference might be caused by the exclusion of duplicated contigs in our research or the use of different annotation methods.…”
Section: Annotation and Evolutionary History Of The Japanese Chestnut...supporting
confidence: 74%
“…However, 69,980 high-confidence genes were predicted in the genome of the cultivar 'Ginyose' (Shirasawa et al, 2021). Compared with the former genome annotation of Chinese chestnut (Table 2), our genome annotation of Japanese chestnut predicted a similar number of gene models as the research conducted by Sun et al (Sun et al, 2020) and predicted more gene models than the research performed by Wang et al (Wang et al, 2020b), Xing et al (Xing et al, 2019) and Hu et al (Hu et al, 2022). Compare the BUSCO scores of these predicted gene sets, more than 193 complete BUSCOs were predicted in the Genome of 'Tsukuba' than that in the Genome of 'Ginyose' (Table 2).…”
Section: Annotation and Evolutionary History Of The Japanese Chestnut...supporting
confidence: 61%
See 3 more Smart Citations